PERANCANGAN DAN ANALISIS JARINGAN WIRELESS DISTRIBUTION SYSTEM PADA FAKULTAS TEKNIK DAN ILMU KOMPUTER UNIVERITAS MUHAMMADIYAH KOTABUMI - Adi Wibowo (LPPM Universitas Muhammadiyah Kotabumi, 2021)
Wireless networks have been widely used for internet services in the business, banking, cafe, military, and education sectors as well as in educational institution such as University of Muhammadiyah Kotabumi. The internet facilities available on campus are used to serve lecturers, education staff and students in accessing the internet. Currently, various models of wireless network technology with the 802.11 standard have now been widely used, both with a frequency of 2.4 GHz and 5 GHz, even computer and smartphone vendors have installed wireless network cards on their products to facilitate user mobility. However, in reality, especially in University of Muhammadiyah Kotabumi, the points of wifi have not been found in all locations.To make it easier to add wifi points, Wireless Distribution System (WDS) technology is used. WDS is a technology that receives signals and radiates back. WDS is used to optimize the use of network resources to cover the service area. Using WDS allows wireless network connection with multiple access points without having to use cables. All access points used for WDS must be configured using the same radio channel and encryption key. Based on the explanation above and looking at the problems that exist in the System and Technology Study Program, Universitas Muhammadiyah Kotabumi, the rsearcher conducted a research entitled Implementation and Analysis of Wireless Distribution System Networks at the Faculty of Engineering and Computer Science, Universitas Muhammadiyah Kotabumi. The computer network that has been implemented is monitored and analyzed. Monitoring and analyzing throughput, delay, and packet loss parameters of the connected WDS network, namely Access point 1, Access point 2, and Access point 3 using Axence Nettools. The measurement results after the WDS network has been implemented are obtained The throughput value is 85%, packet lost is 0.007456 and delay is 0.66ms. Based on the implementation and analysis carried out, it can be concluded that the results obtained meet user expectations by referring to the THIPON standard.